The exoplanetary magnetosphere extension in Sun-like stars based on the solar wind–solar UV relation. Issue 4 (6th January 2023) - Reda, Raffaele; Giovannelli, Luca; Alberti, Tommaso; Berrilli, Francesco; Bertello, Luca; Del Moro, Dario; Di Mauro, Maria Pia; Giobbi, Piermarco; Penza, Valentina
ABSTRACT: The Earth's magnetosphere extension is controlled by the solar activity level via solar wind properties. Understanding such a relation in the Solar system is important for predicting the condition of exoplanetary magnetospheres near Sun-like stars. We use measurements of a chromospheric proxy, the Ca ii K index, and solar wind OMNI parameters to connect the solar activity variations, on decennial time-scales, to the solar wind properties. The data span the period 1965–2021, which almost entirely covers the last five solar cycles. Using both cross-correlation and mutual information analysis, we find a 3.2-yr lag of the solar wind speed with respect to the Ca ii K index. Analogously, a 3.6-yr lag is found once we consider the dynamic pressure. A correlation between the solar wind dynamic pressure and the solar ultraviolet emission is found and used to derive the Earth's magnetopause standoff distance. Moreover, the advantage of using a chromospheric proxy, such as the Ca ii K index, creates the possibility to extend the relation found for the Sun to Sun-like stars, by linking stellar variability to stellar wind properties. The model is applied to a sample of Sun-like stars as a case study, where we assume the presence of an Earth-like exoplanet at 1 au. Finally, we compare our results with previous estimates of the magnetosphere extension for the same set of Sun-like stars.